THEORETICAL BASIS AND PRACTICAL DIRECTIONS OF IMPLEMENTING DUAL EDUCATION IN PEDAGOGICAL HIGHER EDUCATION INSTITUTIONS BASED ON INTERNATIONAL EDUCATIONAL PROGRAMS - Sultonova Gulnoza Rakhimberdi kizi (Modern American Journals, 2025)
This article analyzes the theoretical foundations and practical directions of implementing dual education in pedagogical higher education institutions based on international educational programs. The dual education model ensures a balanced integration of theoretical knowledge and practical skills, playing a key role in the development of professional competencies of future teachers. The article also discusses the advantages of dual education derived from international experience, the existing challenges in its implementation, and possible solutions. The wide application of this model in the higher education system contributes to increasing the efficiency of the pedagogical process, preparing competitive specialists for the labor market, and expanding innovative approaches to teaching and upbringing.
Keywords: dual education, international educational programs, pedagogical higher education, professional competence, innovative learning, quality of education, theory-practice integration.